(untitled) (Research, Society and Development, 2021)
Introduction: Wound healing is a mechanism that involves a sequence of molecular events for the purpose of tissue repair. In this sense, the use of LED and laser phototherapy stands out due to its bio-stimulating characteristics for a cell during the repair process. Objective: to carry out a literature review in order to observe the photobiomodulator effect of red, blue and green lights on collagen during the healing process of burns. Methodology: this is an integrative literature review, carried out in the Pubmed, Web of Science and Lilacs databases. Results: among the 1,721 studies found, only 18 articles, published between 2011 and 2020, were used for the results. Conclusion: The photobiomodulation of red, blue and green lights in the skin burn repair process satisfactory results mainly in relation to collagen production, angiogenesis, reduction of inflammation, reduction of the size of the lesion and stimulation of fibroblasts.